URBAN LIGHTING TECHNOLOGY ADVANCEMENT IN ELECTRICITY ENERGY EFFICIENCY, EVIDENCE: BANDUNG MUNICIPALITY STREET LIGHTS - Gumilar, Yusup; Li, Jun; Juwita, Melda Ria (Redeca, Revista Eletrônica do Departamento de Ciências Contábeis & Departamento de Atuária e Métodos Quantitativos, 2020)
Street lighting (PJU) is one of the critical facilities that have a vital function, it has a very strategic feature. Besides provide night vision for road users, PJU also has a city artistic value that can add to the attractiveness, harmony, beautification as well. Considering to improve PJU services as the aim for the city’s splendor, safety, security for its residents around public roads, also provide significant savings on energy consumption, Bandung Municipality using effective, efficient, and sustainable resources, intends through Light Emitted Diode (LED) as an advancement of PJU technology. To find out how far the reduction in energy consumption and electricity costs charged by PJU, this research measuring through comparison approach both Non-LED PJU and LED PJU electricity payment, in addition, electricity consumption. This research depicts both lamps' evaluation descriptively as well. LED lighting is a combination of solid-state light sources, control gears for LED lighting operations, and optics for light distribution. The parts would influence the performance of LED lighting in terms of energy efficiency, color quality, life, and lumen maintenance. These components affect the quality of the LED lighting itself. With lower electricity power, LED PJU lights are not inferior to conventional PJU lamps' lighting quality, thus, LED PJU conducts high saving energy demand. Moreover, detracts electricity cost at the same time. The expenditure from changing the PJU lamp from Non-LED to LED PJU able to contribute efficiency of both electrical energy and electricity payment slightly above 30% in Bandung municipality.